Sosialisasi Peran Pemerintah Desa Serta Partisipasi Masyarakat dalam Meningkatkan Pertumbuhan Ekonomi di Desa Kuala Bubon - Omalia, Noka; Belgiana, Chi Chi; Fadilah, Erika; Afifah, Nurul; Nurkhairan, Nurkhairan (Pencerah, 2024)
The Community Empowerment Program in the form of education is carried out in collaboration between students of the State Administration Study program and Kuala Bubon village government officials. With the theme